Role difference and negativity bias relevance in strategy review: An experiment - Jesica Handoko; I Made Narsa; Basuki Basuki (Cogent Business & Management, 2021)
This study aims to examine whether there are differences between set roles when reviewing strategy execution in two new regions, especially when the initial period performance achievement is below target. This judgment differences will be explained through attribution theory and negativity bias theory. The 2 x 2 x 2 mixed-subject experimental research design was held during the Covid 19 pandemic involving the assigned roles (as an evaluator or evaluatee), Balanced Scorecard performance achievement (corporate performance indicators below target or above target), and regional managers. The sample consisted of graduate students from the universities in Surabaya who had passed their academic requirement courses and voluntarily participated through web-based media. The research data obtained was analyzed using repeated-measure ANOVA. One hundred and thirty-two participants passed the manipulation check questions and were processed in order to answer the question posed. The results show that there are differences between the structural roles and also when the corporate performance indicators are below target. The evaluator's negative bias is also higher than that of the evaluatee. These findings confirm the relevance of attribution theory and negative bias theory, but the correlation test shows that evaluators also consider external attributes when making strategy reviews. Overall, there is a misalignment between the decision-makers, especially when the performance is in a state of fluctuation.
Keywords: 650; Role; performance achievement; strategy review; balanced scorecard; attribution theory; negativity bias theory